Možnosti uplatnění tuhých zbytků ze spaloven komunálního odpadu - Melicher, Daniel (Vysoké učení technické v Brně. Fakulta chemická, 2017)
V bakalárskej práci je riešená problematika využitia tuhých zbytkov zo spaľovní odpadov, predovšetkým v stavebníctve. Cieľom práce je testovanie rôznych úprav surových tuhých zbytkov zo spaľovní odpadov. Tieto sekundárne materiály boli testované v spojivových systémoch na báze portlandského cementu, sadry, pripravené z chemosadrovca, vápna a v alkalicky aktivovaných systémoch. Cieľom bolo overiť, či je možné tuhé zbytky zo spaľovne odpadov využívať ako zložku alternatívnych materiálov pre stavebný priemysel.

The bachelor thesis deals with the use of solid residues from incineration waste products, especially in the construction industry. The aim of the thesis is to test various modifications of solid residues from incineration waste. These secondary materials were tested in bonding systems based on hydratation of portland cement, gypsum made from chemogypsum, quicklime and alkali-activated systems. The aim was to verify whether solid residues from waste incineration could be used as a component of alternative materials for the construction industry.
Possibilities of application of fluidized bed combustion solid residues from municipal waste
Keywords: Tuhé zbytky zo spaľovne odpadov; portlandský cement; fluidný popolček mletý ložový; chemosadrovec; alkalicky aktivované materiály; Solid residues from the waste incinerator; portland cement; fluidized bed fly ash; chemogypsum; alkali activated materials